High levels of blood glutamic acid and ornithine in children with intellectual disability. (3rd September 2022) - Wasim, Muhammad; Khan, Haq Nawaz; Ayesha, Hina; Tawab, Abdul; Habib, Fazal e; Asi, Muhammad Rafique; Iqbal, Mazhar; Awan, Fazli Rabbi
Abstract : Objectives: Aminoacidopathies are inborn errors of metabolism (IEMs) that cause intellectual disability in children. Luckily, aminoacidopathies are potentially treatable, if diagnosed earlier in life. The focus of this study was the screening of aminoacidopathies in a cohort of patients suspected for IEMs. Methods: Blood samples from healthy (IQ > 90; n  = 391) and intellectually disabled (IQ < 70; n  = 409) children (suspected for IEMs) were collected from different areas of Northern Punjab, Pakistan. An analytical HPLC assay was used for the screening of plasma amino acids. Results: All the samples ( n  = 800) were analyzed on HPLC and forty-three out of 409 patient samples showed abnormal amino acid profiles mainly in the levels of glutamic acid, ornithine and methionine. Plasma concentration (Mean ± SD ng/mL) were significantly high in 40 patients for glutamic acid (patients: 165 ± 38 vs. controls: 57 ± 8, p  < 0.00001) and ornithine (patients: 3177 ± 937 vs. controls: 1361 ± 91, p  < 0.0001). Moreover, 3 patients showed abnormally high (53.3 ± 8.6 ng/mL) plasma levels of methionine. Conclusion: In conclusion, biochemical analysis of samples from such patients at the metabolites level could reveal the underlying diseases which could be confirmed through advanced biochemical and genetic analyses. Thus, treatment to some of such patients could be offered. Thus burden of intellectual disability caused by such rare metabolic diseases could be reduced from the target populations.